Growth, Yield and Quality of Maize under Ozone and Carbon Dioxide Interaction in North West India - Achchhelal Yadav; Arti Bhatia; Sudesh Yadav; Archana Singh; Ritu Tomer; Ramesh Harit; Vinod Kumar; Bhupinder Singh (Aerosol and Air Quality Research)
Abstract Maize is an important C4 crop and how it will respond to elevated atmospheric carbon dioxide and ozone levels is not well documented. To understand how the growth and nutritional quality of maize will be affected under elevated carbon dioxide (CO2) and tropospheric ozone (O3) interaction, a field experiment was conducted under free air O3 and CO2 enrichment rings (FAOCE) growing HQPM-1 and PMH-1 maize cultivars at New Delhi, India. Each cultivar was exposed to ambient and elevated CO2 (559 ppm) alone and along with ambient and elevated O3 (71.8 ppb) throughout the growing period. Elevated CO2 (EC) significantly increased the leaf area index (10.8–22.5%), chlorophyll (11.2–17.3%) and photosynthetic rate (12.1–16.5%) in the two cultivars over the ambient. O3 exposure of 27 ppm hr (AOT4O) under elevated O3 (EO) treatment led to a significant decline in yield (p < 0.01) by 9.2% in HQPM-1 and 9.8% in PMH-1. Under elevated CO2 the increase in grain yield was higher under HQPM-1 (25.4%) as compared to PMH-1 (9.04%). The protein content increased under EO (8.1–12.5%) and decreased under EC (13.4–13.6%) in the two maize cultivars due to yield dilution effect. Lysine, phosphorus and potassium content of the grain significantly decreased in both the cultivars under elevated CO2. Carbohydrate and amylose concentrations in grains increased (9.9–15.5%) under EC and decreased (10.8–16.7%) under EO, however, no significant change in yield, protein, amylase, carbohydrate, lysine, potassium and phosphorus was observed under the interaction treatment ECO as compared to the ambient. After two years of study we could conclude that elevated CO2 (559 ppm) was able to offset the negative effect of elevated O3 (71 ppb) on grain yield by 11.2% in PMH-1 and by 18.8% in HQPM-1 without significantly affecting the grain quality in both the maize cultivars.